2018
DOI: 10.3390/w10050648
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pb2+ from Water by Synthesized Tannin Resins from Invasive South African Trees

Abstract: Contamination of water by Pb2+ and the threat of invasive vegetation affects the quality and quantity of water accessible to all life forms and has become a primary concern to South Africa and the world at large. This paper synthesized, characterized, and evaluated the resins from tannin-rich invasive Acacia species as an environmentally benign Pb 2+ adsorbent. The analysis of the pore volume and surface area of the resins reveals a small pore dimension of 9 × 10 −3 cc/g and large surface area (2.31-8.65 m 2 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Thus, the results demonstrate excellent selectivity of TA-capped AuNPs toward Pb 2+ ions among all interfering metal ions. The results obtained in this study are in accordance with previously reported data on strong adsorption capacity of tannin compounds toward Pb 2+ ions in comparison to other metal [49,50].…”
Section: Selectivitysupporting
confidence: 93%
“…Thus, the results demonstrate excellent selectivity of TA-capped AuNPs toward Pb 2+ ions among all interfering metal ions. The results obtained in this study are in accordance with previously reported data on strong adsorption capacity of tannin compounds toward Pb 2+ ions in comparison to other metal [49,50].…”
Section: Selectivitysupporting
confidence: 93%
“…Avagadro number (6.019 × 10 23 ) and A is the area per molecule on the surface which is 130Å 2 (corresponding to the molecule lying flat on the adsorbent surface). The value of SSA calculated, 43.689m 2 /g, is greater than those of silver wattle tannin resin (STR), green wattle tannin resin (GTR) and black wattle tannin resin (BTR)[58]. However, the SSA value obtained for tannin resin derived from Mimosa tannin (MTR), 139.2 m 2 /g, is greater than that of CATAR[59].…”
mentioning
confidence: 84%
“…Acacia-mimosa plays an important commercial role since its wood can be used for the paper production through the kraft process by the amount of cellulose present in the material [267], allowing the elaboration of several products like cardboard, the paper for writing and printing, which gives it a special shine, considered of high quality, and more advantageous than eucalyptus due to the low amount of alkali it presents [263], and finally, acacia wood is also used for the production of construction materials and furniture, compounds of interest to the medicinal sector [289,290], xylooligosaccharides [291], syringaldehyde, vanillin [292], and solutions rich in glucose [293,294]. The bark is used for the production of tannins (substances of plant origin) due to the high amount present in the species (greater than 74%) [295] and other compounds such as absorbents [296], those with an antimicrobial and antioxidant capacity [266,297] and the anti-quorum sensing [298]. In the perfume industry, flowers are processed to produce fragrances, as well as perfume fixatives [263], in the production of compounds with anti-inflammatory properties [299,300] as well as other types of products such as bioherbicides [301].…”
Section: Acacia (Acacia Dealbata L)mentioning
confidence: 99%